Physical modelling of liquefiable soils in shaking table (2016)
The dynamic models are widely used to estimate the soil behaviour during earthquakes. These models are useful to validate numerical data or to understand failure mechanisms induced in that kind of events. During the quake are generated additional stress and in some cases the extra load can reduce the shear strength of the material. Furthermore, in saturated sandy soils is produced an excess pore pressure which could induce a failure by liquefaction. The liquefaction can be evaluated through several laboratory methods, but not all techniques represent totally the phenomenon. This research work addresses the design, construction and implementation of a flexible container capable to simulate the liquefaction phenomena by shaking table at 1g. The equipment was instrumented with a one pore pressure sensor, one displacement transducer, two accelerometers and one piezoelectric actuator. An experimental program was developed, which incorporated three different size particles of Guamo sand. The soil was tested in the device with the purpose to evaluate the liquefaction susceptibility. In addition, the experimental program also included the application of three fundamental frequencies from representative earthquakes in Colombia at three different amplitudes for a scaling of 1,50 and 80g.